Pengaruh Kepemimpinan dan Motivasi Kerja Kiyai Terhadap Kinerja Guru di Pondok Pesantren Modern Hidayatussalikin Pangkalpinang Bangka Belitung - Usman Afandi (EDOIS: Journal of Islamic Education, 2023)
This research examines the leadership and work motivation of kiyais on the performance of teachers at the Hidayatussalikin modern Islamic boarding school in Pangkalpinang Bangka Belitung, which was established in 1973 until now. Ahmad Ja'far Shidiq M.Pd who comes from the island of Java. The Hidayatussalikin Islamic Boarding School itself, at the beginning of its transformation into a boarding school in 2008, has accepted more than one hundred (100) new students who live in the boarding school with a total teaching staff of twenty-five (25) ustad and ustazah. Therefore, it is important to conduct research on the leadership and work motivation of kiyai on teacher performance in the modern Islamic boarding school Hidayatussalikin Pangkalpinang Bangka Belitung to study more deeply the influence of the leadership and work motivation of kiyai on teacher performance in the Islamic boarding school Hidayatussalikin Pangkalpinang Bangka Belitung. This type of research is in the quantitative genre, and when combined with the research approach used, it is descriptive-quantitative. The population was taken from all teachers (ustad and ustazah) with the criteria of teachers who have worked for more than two (2) years, for a total of forty-two (42) people. The technique used in sampling in this study used a purposive sampling method, so that the number of populations became a reference for researchers to determine as many samples as the population, namely the number of samples as many as forty-two (42) respondents. Based on the study's results, the Kiyai Leadership variable has a positive and significant effect on teacher performance at the Hidayatussalikin modern Islamic boarding school Pangkalpinang Bangka Belitung. This is shown by a significance value of 0.000 <0.05 and a tcount value of 7.760 > ttable 1.681, which equals 61.1%. At the Hidayatussalikin modern Islamic boarding school in Pangkalpinang Bangka Belitung, the Kiyai Work Motivation variable has a positive but not significant effect on teacher performance. This is shown by a significance value of 0.071 <0.05 and a tcount value of 1.858 > ttable 1.681, which is a percentage of 7.9%. The results are not normally distributed. Furthermore, in terms of obtaining the test results simultaneously or together, the two variables above have a positive and significant effect on the teacher performance variable. In terms of obtaining a significance value of 0.000 <0.05, it is found that the acquisition of an fcount value is 30.689 > ftable 3.238 with a percentage of influence of 61, 1%.